SAT0481 Clinical Factors for Incident Vertebral Fractures Treated with Bisphosphonates in Glucocorticoid-Induced Osteoporosis. Who Needs to Use Other Anti-Osteoporotic Agents?. (10th June 2014) - Ushikubo, M.; Kuda, H.; Ito, H.; Izumi, K.; Tamaki, S.; Akiya, K.; Tanaka, I.; Oshima, H.
Abstract : Background: Although bisphosphonates (BP) is a popular choice for prevention and treatment of Glucocorticoid-induced osteoporosis (GIO), other agents such as teriparatide (TPT) or denosmab have been also available for the treatment. Based on an aspect of health economics, BP would be a first lime of the choice for prevention and treatment of GIO. On the other hands, the effect of TPT was reduced when TPT was started after a long term treatment of BP. Therefore, it would be best if we distinguish a population that did not receive the anti-osteoporotic effect of BP. Objectives: To clarify clinical factors which correlated with incident fractures in patients treated with BP, and distinguish patients who need other anti-osteoporotic agents. Methods: Patients (n=137) with connective tissue diseases other than rheumatoid arthritis were recruited and observed for 2 years. The means of age, disease duration, total prednisolone (PSL) dosage, and daily PSL dosage during the study period were 61±15 (SD), 12±11 years, 34±34g, and 8±6mg/day, respectively. Prevalent vertebral fractures were seen in 44% of the patients. Agents used for prevention and treatments of GIO were BP (54%), active vitamin D3 (7%), vitamin K2 (6%). Bone mineral densities (BMD) were measured with DXA at the distal radius. Results: 1) Incident vertebral fractures determined with deteriorating grades by the SQ method were seen in 64 patients (47%). 2) Logistic regression analysis showed the age (1.43 (OR)/5yo), total PSL dosage (1.09/5g), daily PSL dosage (2.36/5mg), and BMD (1.25/5% decrease) as independent risk factors, and treatments with BP (0.02) and vitamin K2 (0.06) as preventing factors (P<0.05). 3) Analysis of 74 patients with BP, incident fractures were seen in 22 patients (30%). Among those patients with incident fractures, the age was higher and the BMD was lower than those without incident fractures. Multivariable analysis with logistic regression revealed the presence of prevalent fracture (OR3.6), the higher daily PSL dosage during the study period (OR1.7/5mg), and the lower BMD (OR1.6/5%) as independent risk factors. Conclusions: Patients treated with BP in GIO, the presence of prevalent fractures, the higher daily PSL dosages, and the lower BMD were risk factors for incident vertebral fractures. An further treatment may be needed in those patients. References: Nawata et al. J Bone Miner Metab 23:105-109. Saag et al. Arthritis Rheum 60:33-46. Grossman et al. Athritis Care Res 62:1515-1526. Ettinger et al. J Bone Miner Res 19:745-751. Abrahamsen et al. Osteoporos Int 24: 321-328. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4798